ANALISIS TINGKAT KEANDALAN SISTEM PROTEKSI KEBAKARAN BANGUNAN GEDUNG DI KANTOR PENCARIAN DAN PERTOLONGAN SEMARANG - Laurentina Grace Silva; Suroto Suroto; Daru Lestantyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
This building is included in a state building, which has fire risk and has to be anticipated with fire protection system from fire hazard that meets the requirements of Occupational Safety and Health (K3). Some of the high risk areas for fires are fuel warehouses, communication center room and generator room. In 2015 this building was recorded as having experienced electrical short circuit in its electrical system, causing a fire in the electrical panel. This study aims to analyze the level of reliability of fire protection systems in the Semarang Search and Rescue Office building. This type of research was descriptive qualitative that describes and analyzes objects according to the conditions of the study. The subject of this study was divided into two, namely the main informant and triangulation who have varied positions and selected using purposive sampling method. This study used the PD-T-11-2005-C data collection guidelines or guidelines for building fire safety checks issued by the Ministry of Public Works of the Republic of Indonesia. The results of this study indicate that the reliability level of fire protection systems in Semarang Search and Relief Office was 73.83% in the adequate category, so it is necessary to increase the fulfillment of components, especially in fulfilling fire hydrant and detection and fire alarms in buildings.